MEMBANGUN BRAND EQUITY UMKM IKAN ASAP MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY MELALUI LITERASI PEMASARAN - Ajrun 'Azhim Al As'hal; Egen Hardika Kurniawan (Program Studi Manajemen Bisnis Syariah, 2024)
Abstrak UMKM merupakan salah satu roda penggerak perekenomian nasional. Terbukti bahwa UMKM telah membantu 61,97% PDB Indonesia. Namun sayangnya, masih banyak produsen yang memiliki cara kuno dalam memasarkan dan mempromosikan produknya. Sehingga produk yang dijual hanya diketahui dan dikenal di daerah sekitar. Maka dari itu dibutuhkan cara dan alternatif baru dalam memasarkan dan mempromosikan produk UMKM khususnya produk UMKM ikan asap di Kawasan Pantai Prigi. Penelitian ini bertujuan untuk membedah apa saja cara yang bisa digunakan untuk membangun brand equity UMKM ikan asap di Kawasan Pantai Prigi Tenggalek, bagaimana penerapan teknologi augmented reality melalui literasi pemasaran pada pelaku UMKM serta keefektifan penggunaan teknologi augmented reality dalam meningkatkan pemasaran ikan asap di Kawasan Pantai Prigi Tenggalek Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian, diperoleh bahwa teknologi augmented reality efektif bagi para pelaku UMKM ikan asap dalam membangun brand equity, produk UMKM dapat dipromosikan dan dipasarkan melalui pengoptimalan teknologi augmented reality seperti menggunakan aplikasi layar, instagram, facebook, dan tiktok. Adanya brand equity dapat membantu menjangkau para konsumen yang berada di luar daerah, brand equity menjadikan produk ikan asap di Kawasan Pantai Prigi dapat meningkat dan terus berkembang. Kata kunci: brand equity, teknologi augmented reality, UMKM, literasi pemasaran Abstract UMKM are one of the driving wheels of the national economy. It is proven that UMKM have helped 61.97% of Indonesia's GDP. But unfortunately, there are still many manufacturers who have old-fashioned ways of marketing and promoting their products. So the products sold are only known and recognized in the surrounding area. Therefore, new ways and alternatives are needed in marketing and promoting MSME products, especially smoked fish MSME products in the Prigi Beach Area. This research aims to dissect what methods can be used to build brand equity for smoked fish UMKM in the Prigi Tenggalek Beach Area, how to apply augmented reality technology through marketing literacy to UMKM and the effectiveness of using augmented reality technology in increasing the marketing of smoked fish in the Prigi Beach Area Tenggalek This research uses a qualitative approach. Data collection techniques through observation, interviews and documentation. Based on the research results, it was found that augmented reality technology is effective for smoked fish UMKM in building brand equity, MSME products can be promoted and marketed through optimizing augmented reality technology such as using screen applications, Instagram, Facebook and TikTok. The existence of brand equity can help reach consumers outside the region. Brand equity means that smoked fish products in the Prigi Beach area can increase and continue to develop.UMKM are one of the driving wheels of the national economy. It is proven that UMKM have helped 61.97% of Indonesia's GDP. But unfortunately, there are still many manufacturers who have old-fashioned ways of marketing and promoting their products. So the products sold are only known and recognized in the surrounding area. Therefore, new ways and alternatives are needed in marketing and promoting MSME products, especially smoked fish MSME products in the Prigi Beach Area. This research aims to dissect what methods can be used to build brand equity for smoked fish UMKM in the Prigi Tenggalek Beach Area, how to apply augmented reality technology through marketing literacy to UMKM and the effectiveness of using augmented reality technology in increasing the marketing of smoked fish in the Prigi Beach Area Tenggalek This research uses a qualitative approach. Data collection techniques through observation, interviews and documentation. Based on the research results, it was found that augmented reality technology is effective for smoked fish UMKM in building brand equity, MSME products can be promoted and marketed through optimizing augmented reality technology such as using screen applications, Instagram, Facebook and TikTok. The existence of brand equity can help reach consumers outside the region. Brand equity means that smoked fish products in the Prigi Beach area can increase and continue to develop.UMKM are one of the driving wheels of the national economy. It is proven that UMKM have helped 61.97% of Indonesia's GDP. But unfortunately, there are still many manufacturers who have old-fashioned ways of marketing and promoting their products. So the products sold are only known and recognized in the surrounding area. Therefore, new ways and alternatives are needed in marketing and promoting UMKM products, especially smoked fish UMKM products in the Prigi Beach Area. This research aims to dissect what methods can be used to build brand equity for smoked fish UMKM in the Prigi Tenggalek Beach Area, how to apply augmented reality technology through marketing literacy to UMKM and the effectiveness of using augmented reality technology in increasing the marketing of smoked fish in the Prigi Beach Area Tenggalek This research uses a qualitative approach. Data collection techniques through observation, interviews and documentation. Based on the research results, it was found that augmented reality technology is effective for smoked fish UMKM in building brand equity, UMKM products can be promoted and marketed through optimizing augmented reality technology such as using screen applications, Instagram, Facebook and TikTok. The existence of brand equity can help reach consumers outside the region. Brand equity means that smoked fish products in the Prigi Beach area can increase and continue to develop. Keywords: brand equity, augmented reality technology, UMKM, marketing literacy